Gender and inorganic nitrogen: what are the implications of moving towards a more balanced use of nitrogen fertilizer in the tropics? - Farnworth, Cathy Rozel; Stirling, Clare M.; Sapkota, Tek Bahadur; Jat, Mangi Lal; Misiko, Michael T.; Simon, Attwood (Informa UK Limited, 2017)
For agriculture to play a role in climate change mitigation strategies to reduce emissions from inorganic nitrogen (N) fertilizer through a more balanced and efficient use are necessary. Such strategies should align with the overarching principle of sustainable intensification and will need to consider the economic, environmental and social trade-offs of reduced fertilizer-related emissions. However, the gender equity dimensions of such strategies are rarely considered. The case studies cited in this paper, from India, Lake Victoria in East Africa and more broadly from sub-Saharan Africa (SSA), show that the negative externalities of imbalanced inorganic N use in high- and low-use scenarios impact more strongly on women and children. We examine, through a literature review of recent work in SSA, the relative jointness of intra-household bargaining processes in low N use scenarios to assess the degree to which they impact upon N use. We suggest that gender-equitable strategies for achieving more balanced use of N will increase the likelihood of attaining macro-level reductions in GHG emissions provided that they secure equity in intra-household decision-making and address food security. Gender-equitable N use efficiency strategies will help to integrate and assure gender and social equity co-benefits at local scales.